2005
DOI: 10.2139/ssrn.855064
|View full text |Cite
|
Sign up to set email alerts
|

Are Long-run Price Stability and Short-run Output Stabilization All that Monetary Policy can Aim for?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 72 publications
1
38
0
Order By: Relevance
“…adjust actual unemployment to the NAIRU, Arestis/Sawyer (2004a, 2004b, 2005, Fontana/Palacio-Vera (2007), Hein (2004Hein ( , 2006aHein ( , 2007, and Palacio-Vera (2005) have argued that monetary policy interventions will not be able to constrain instability in many cases for several reasons. Finally, long-run endogeneity of the NAIRU with respect to actual unemployment, and hence to macroeconomic and monetary policies, has been related to different channels.…”
Section: Considering the Ncm Recommendation Of Inflation Targeting Momentioning
confidence: 99%
See 1 more Smart Citation
“…adjust actual unemployment to the NAIRU, Arestis/Sawyer (2004a, 2004b, 2005, Fontana/Palacio-Vera (2007), Hein (2004Hein ( , 2006aHein ( , 2007, and Palacio-Vera (2005) have argued that monetary policy interventions will not be able to constrain instability in many cases for several reasons. Finally, long-run endogeneity of the NAIRU with respect to actual unemployment, and hence to macroeconomic and monetary policies, has been related to different channels.…”
Section: Considering the Ncm Recommendation Of Inflation Targeting Momentioning
confidence: 99%
“…2 Therefore, the long-run Phillips curve becomes vertical. Monetary policy applying the interest rate tool is able to stabilise output and employment in the short run, but in the long run it is neutral and only affects inflation (Fontana/Palacio-Vera 2007). Fiscal policy is downgraded and is restricted to support monetary policies in achieving price stability (Arestis/Sawyer 2003).…”
Section: Introductionmentioning
confidence: 99%
“…All of these authors, and Fair's research as well, have suggested that the U.S. economy has historically operated well within this theorized horizontal range and below full utilization of capacity. Furthermore, in the simulations it need not be the case that productive capacity has not increased with sales and production; in the Fairmodel and consistent with most heterodox analyses, rising sales demand can encourage greater capital accumulation (see the discussion and literature reviews in Palacio-Vera (2005, especially 754-758) and in Fontana and Palacio-Vera (2005)). …”
Section: Macroeconomic Effects Of the Simulated Elr Programmentioning
confidence: 80%
“…Under the assumption that apparently impotent policy effect is due to the mixture of different responses of various workforce groups, workers 1. Many studies such as Erceg and Levin (2014), Fontana and Palacio-Vera (2007), Fontana (2006), Gali (2011), Reifschneider et al (2015) advocated that monetary policy should play a role in preventing employment hysteresis effect. Taylor (2011), on the contrary, blamed the Fed that '[they] used the full employment mandate to justify discretionary policy ….…”
Section: Introductionmentioning
confidence: 99%